Extensão universitária: indicadores para avaliar seu impacto na transformação social - Dantas, Denise Cunha (2019)
The objective of this paper is to propose indicators for the evaluation of the fifth guideline for University Extension actions defined by FORPROEX (Forum of Extension Dean of Brazilian Universities), impact on social transformation. In order to achieve this objective, three UFRJ extension projects were evaluated and categories were established to support the evaluation indicators. These objectives pose the question to be answered by this project: How to establish indicators and their respective categories for the evaluation of the fifth guideline of the University Extension "Impact on Social Transformation"? The motivation for choosing the topic, in the first place, is due to my practice as a researcher, a technical-administrative employee for thirty- two years at the Federal University of Rio de Janeiro. Secondly, my perception that University extension is one of the spaces in which the Public University fulfills its social role. I intended to contribute to the analysis of University Extension Projects as to their effectiveness in strengthening the dialogue between the Academy and the Community outside the University in the aspects of transformation for the action of disadvantaged and excluded social groups. To seek answers to the question presented and to broaden my view on the subject of work, I chose to conduct a participatory social survey. The observation was made from the inclusion of the researcher in the activities of the projects studied in order to preserve their participation and exchange in the field in order to contribute to the development and planning of future actions. From this observation, the participants’ life pictures were seen, felt, described, reconstructed and presented to interpretation through the use of interview and narrative tools for data collection and data analysis, I opted for the content analysis methodology. The indicators established for the proposed evaluation were dialogicity, participation and emancipation, obtained through the valorization of a theoretical basis, in agreement with the studied authors. Empowered by the concepts of the defined indicators I established their respective categories originated from an empirical work.